Effect of nitrogen type on carbon dot photocatalysts for visible-light-induced atom transfer radical polymerization. Issue 20 (6th May 2021) - Hao, Qianqian; Qiao, Liang; Shi, Ge; He, Yanjie; Cui, Zhe; Fu, Peng; Liu, Minying; Qiao, Xiaoguang; Pang, Xinchang
Abstract : N-Doping significantly enhanced the photo-activity of carbon dots. But only pyridinic N can improved the activity of CDs as catalysts for photo-induced ATRP, compared with pyrrolic N and graphitic N. Abstract : Recently, carbon dots (CDs) have been utilized as efficient and environmentally friendly catalysts for photo-induced atom transfer radical polymerization (ATRP) and reversible addition–fragmentation chain-transfer (RAFT) polymerization. Here, we have explored the effect of N types in CDs on photo-induced ATRP, as N is a typical dopant for CDs and may result in an upward shift of the Fermi level and a change in the optical properties. N-Doping significantly enhanced the UV-vis absorption of CDs, resulting in the CDs catalyzing broadband-light induced ATRP. Pyridinic N proved to be key for improving the activity of CDs as catalysts for photo-induced ATRP, compared with pyrrolic N and graphitic N. Even in N-doped CDs with mixed types of N atoms, the ratio of pyridinic N also seriously affected the polymerization rate. This work is of great importance for the application of CDs as photocatalysts for the RDRP system, and to promote the progress of green catalytic polymerization.